Review of Metasurface Antennas for Computational Microwave Imaging - Imani, Mohammadreza F.; Gollub, Jonah N.; Yurduseven, Okan; Diebold, Aaron V.; Boyarsky, Michael; Fromenteze, Thomas; Pulido-Mancera, Laura; Sleasman, Timothy; Smith, David R. (IEEE transactions on antennas and propagation, 2020)
This article covers recent advances in the fusion of metasurface antenna design and computational imaging (CI) concepts for the realization of imaging systems that are planar, fast, and low cost. We start by explaining the operation of metamaterial antennas which can generate diverse radiation patterns. Their advantages and distinctions from previous antennas are elucidated. We then provide an intuitive overview of the CI framework and argue that metamaterial antennas are a near ideal platform for implementing such schemes at microwave frequencies. We describe two metamaterial antenna implementations: frequency diverse and electronically reconfigurable. The tradeoffs governing the design and operation of each architecture are examined. We conclude by examining the outlook of metamaterial antennas for microwave imaging and propose various future directions.